Idealisme dan Ideologi Politik Praktisi Media Bandung TV - Novrizon Marzal (Jurnal Inovasi Komunikasi, 2025)
Abstract. . Bandung as one of the big cities in Indonesia certainly an interest markets for economic and political actors. Bandung Tv’s media through the special rubric dialogue prove this by scooping up benefits directly from the speaker. The aim of this study to know idealism, political ideology, and efforts to negotiate media practitioners Bandung Tv special rubric dialogue. This research uses qualitative methods with a case study based on critical media theory and combined with various other supporting concepts and theories, so can measure the value of idealism and political ideology. The results of the study found; idealism is limited to the individuals, that cannot be continued to their professions, there is no prominent political ideology but leads to the media political economy ideology, and no role for the gatekeeper should oversee negotiations. Value of idealism and political ideology of each individual media practitioners of special rubric dialogue were not seen, it was covered by the power of Bandung Tv’s media director, or has uccurred workers commodification..